Efficacy of oral versus vaginal progestogens for early pregnancy maintenance in women with recurrent miscarriages: a randomized controlled trial - Laiyla Shinwari; Afrah Aman; Mehwish Syed; Rabia Nawaz; Rehana Rahim (Khyber Medical University Journal, 2024)
OBJECTIVE: To compare the effectiveness of oral and vaginal progestogens in the maintenance of early pregnancy in women with recurrent miscarriages.